PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (DINAS PEKERJAAN UMUM, PERUMAHAN RAKYAT KAB. PUNCAK JAYA) - firdaus, yan; nu graha, andi; surjati, endang (Jurnal Riset Mahasiswa Manajemen, 2024)
Abstract This research aims to determine the influence of organizational culture and work motivation on employee performance. This research uses quantitative methods, using saturated sampling, namely 97 employees of the Dinas Pekerjaan Umum, Perumahan Rakyat Kab. Puncak Jaya. The data analysis used is multiple linear regression. The research results show that organizational culture and work motivation can improve employee performance, organizational culture can improve employee performance, work motivation can improve employee performance. Suggestions for improving employee performance need to pay attention to effectiveness with initiative in carrying out tasks.